2020
DOI: 10.1016/j.prevetmed.2020.105197
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for serological evidence of MERS-CoV in camels, Kenya, 2016–2017

Abstract: Middle East Respiratory Syndrome Coronavirus (MERS-CoV) is an emerging viral disease and dromedary camels are known to be the source of human spill over events. A cross-sectional epidemiological surveillance study was carried out in Kenya in 2017 to, 1) estimate MERS-CoV antibody seropositivity in the camel-dense counties of Turkana, Marsabit, Isiolo, Laikipia and Nakuru to identify, and 2) determine the risk factors associated with seropositivity in camels. Blood samples were collected from a total of 1421 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…= 414) had a 51% positivity, and the upper Eastern region (n = 1964, pos. = 1510) had a 77% positivity (Gardner et al, 2019;Ommeh et al, 2018;Sitawa et al, 2020). Spatial correlation of MERS-CoV extended a distance of roughly 400 km across the upper Rift Valley and Eastern regions between 2016 and 2018.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…= 414) had a 51% positivity, and the upper Eastern region (n = 1964, pos. = 1510) had a 77% positivity (Gardner et al, 2019;Ommeh et al, 2018;Sitawa et al, 2020). Spatial correlation of MERS-CoV extended a distance of roughly 400 km across the upper Rift Valley and Eastern regions between 2016 and 2018.…”
Section: Resultsmentioning
confidence: 94%
“…Given that much of the socio-demographic data were from after 2010 and that the MERS-CoV data in the upper Northeastern region were only from 2008, we focused the spatial correlation analysis of MERS-CoV on 2016 through 2018 in the upper Rift Valley and upper Eastern Regions. The 2016-2018 MERS-CoV data were reported without (Corman et al, 2014;Gardner et al, 2019;Ommeh et al, 2018;Sitawa et al, 2020) specifying the date or year that each observation was collected and we therefore spatially analyzed the data as representing a single unit of time (i.e., 3-year time period). Further, we distributed the data evenly between the northern and southern parts of each county to satisfy the practical rule that a variogram should only be applied over a specified distance for which the number of pairs is greater than 30, and because the data were not further spatially identified (Journel and Huijbregts, 1978).…”
Section: Data Analysis Model Evaluation and Selectionmentioning
confidence: 99%
“…Though MERS is only endemic in the Middle East and an outbreak has never been detected in Kenya, MERS has been declared a priority pathogen by the World Health Organization with acknowledgement of seropositivity in camels throughout Kenya [ 43 , 44 ]. A recent study by Sitwa et al found a 69% seropositivity rate among camels in Kenyan pastoral systems, indicating potential transmission risk for people in contact with camels [ 45 ]. Shifting trends in herd composition, stemming from climate and herder preference, suggests new possible risk factors [ 19 ].…”
Section: Discussionmentioning
confidence: 99%